Review of family‐based treatments from 2010 to 2019 for suicidal ideation and behavior. (28th October 2021) - Frey, Laura M.; Hunt, Quintin A.; Russon, Jody M.; Diamond, Guy
Abstract: Suicide ideation and behavior are pervasive public health issues. Given that positive interpersonal relationships can be a protective factor against suicide risk, we conducted a systematic review to examine peer‐reviewed publications from 2010 to 2019 that included empirical data, tested an intervention with at least some family component, and included a suicide‐related outcome measure. We reviewed and synthesized findings from 22 articles covering 7 intervention categories with 12 interventions to examine the treatment components and the quality of evidence to support them. Using Southam‐Gerow and Prinstein's ( Child Adolesc Psychol 43:16, 2014) guidelines, we identified two well‐established intervention categories that met the highest standards for interventions and three probably efficacious intervention categories. All interventions found focused solely on suicide risk in adolescent populations. More studies are needed for adult populations and to explore the role of family moderators and mediators to test whether suicide outcomes are reduced by improvement in the family environment.